Evaluation of a Gamified 3D Virtual Reality System to Enhance the Understanding of Movement in Physics - Becerra, DAI (2017)
The creation of new technological tools in education provides different learning opportunities to students. The present research evaluates an application that we have developed for the use of virtual reality to enhance the understanding of movement in physics, using gamification techniques on the application allowed us to improve the motivation of the students to learn, the validation of this research was made using a methodology to evaluate the didactic value of educational software, and this evaluation was carried out on a group of teachers.